СӨЗ ҲӘМ ТОПОНИМ ТҮСИНИГИ (Хожели районы топонимлери мысалында) - Есемуратов, А.Е. (FAN va JAMIYAT, 2023)
In this article, the author examines one of the most pressing problems of modern onomastics - the phenomenon of words and toponyms. The word has a lexical meaning. The similarity of the meaning of the word with historical changes is present in all languages, because it depends on changes in human society.